Impact of agro-geotextiles on soil aggregation and organic carbon sequestration under a conservation-tilled maize-based cropping system in the Indian Himalayas - Roy, Plabani; Bhattacharyya, Ranjan; Singh, Raman Jeet; Sharma, N. K.; Kumar, Gopal; Madhu, M.; Biswas, D. R.; Ghosh, Avijit; Das, Shrila; Joseph, Ann Maria; Das, T. K.; Kumar, Soora Naresh; et al. (Frontiers in Environmental Science, 2023)
Although agro-geotextile (AGT) emplacement has potential effect to mitigate soil loss and thus increase carbon sequestration, comprehensive information is scanty on the impact of using agro-geotextiles on soil organic carbon (SOC) sequestration, aggregate-associated C and soil loss in the foothills of the Indian Himalayan Region. We evaluated the impacts of Arundo donax AGT in different configurations on SOC sequestration, aggregate stability and carbon management index (CMI) since 2017 under maize-based cropping systems on a 4% land slope where eight treatments were adopted. Results revealed that Arundo donax placement at 0.5 m vertical interval-pea-wheat treatment (M+AD10G0.5-P-W) had ~23% increase in SOC stock (27.87 Mg ha -1 ) compared to maize-wheat system (M-W) in the 0-30 cm soil layer. M+AD10G0.5-P-W and maize-pea-wheat under bench terracing (M-P-W)BT had similar impacts on SOC stocks in that layer after 5 years of cropping. Total SOC values in bulk soils, macroaggregates and microaggregates were ~24, 20, and 31% higher, respectively, in plots under M+AD10G0.5-P-W than M-W in the topsoil (0-5 cm). The inclusion of post-rainy season vegetable pea in maize-wheat cropping system along with AGT application and crop residue management generated additional biomass and enhanced carbon management index (CMI) by ~60% in the plots under M+AD10G0.5-P-W over M-W, although M+AD10G0.5-P-W and (M-P-W)BT had similar effects in the topsoil. In the 5-15 cm layer, there was no significant effect of soil conservation practices on CMI values. In M+AD10G0.5-P-W treatment, the annual mean soil loss decreased by ~92% over M-W treatment. We observed that CMI, proportion of macroaggregates, aggregate-associated C, labile C, total SOC concentration (thus SOC accumulation rate) and mean annual C input were strongly correlated with mean annual soil loss from 2017 to 2021. The study revealed that emplacement of Arundo donax mat and incorporation of a legume in a cropping system (M-W), conservation tillage and crop residue retention not only prevented soil loss, but also enhanced C sequestration compared to farmers' practice (M-W) in the Indian Himalayas. The significance of this study is soil conservation, recycling of residues and weeds, climate change adaptation and mitigation as well as increasing farmers' income.